Sociology of Law in the Perspective of Roscoe Pound and Donald Black and its Relevance in the Indonesian Context - Ahmad Qiram As-Suvi; Moh. Zainullah (Pustaka Peradaban, 2022)
This article aims to identify and analyze Roscoe Pound's thoughts on sociological jurisprudence, besides that this article also aims to identify and analyze Donald Black's legal sociology thoughts, as well as the actualization of Pound and Black's thoughts in the Indonesian context. The approach method used in this article is a literature study with a qualitative descriptive approach, while the results in this article show that Pound's sociological jurisprudence and Black's sociology of law both approach law through the discipline of sociology, even though the legal concepts they produce are different. . Pound with the concept of interest, social engineering while Black with the concept of law as a quantitative variable in his magnum opus The behavior of law. They both also think that the law is a tool of social control and seems to want to perceive that the law does not always talk about articles, but there are other important aspects that must be considered.